Analisisyuridis Upaya Harmonisasi Antar Lembaga Penyidikan Tindak Pidana Korupsi di Indonesia - Ansori ANSORI (KEADILAN PROGRESIF, 2017)
Efforts to the eradication of corruption in Indonesia is carried out for a long time, since the era of the Old Order to the Order Reforms. Significant changes in the understanding and eradication of corruption occurs when the Corruption Eradication Commission (KPK) was formed in 2002 by Act No. 30 of 2002. The establishment of the KPK as an institution are authorized to investigate corruption as the competencies of Police and Attorney. It should be a driving force in the eradication of corruption. Ideally this momentum can be used by other agencies for the investigation of criminal corruption to go hand in hand and give each other encouragement and support so that the corruption in Indonesia can be reduced in number. Apparently, some of the facts shows that the opposite occurs alleged feud "Lizard vs Crocodile" is the momentum for mutual criminalize of the corruption investigation agencies. Disharmony in the investigation of criminal corruption agencies do not supposed to happen because there are laws of each institution to limit each one. Besides, it is necessary for the good cooperation in the eradication of corruption among institutions especially the KPK, the Police and the Attorney so that the number of corruption can be reduced and the corruption can be eradicated from Indonesian society.